Legal and institutional arrangements for combating child trafficking in Harare, Zimbabwe. - Musanhu, Belinda Rutendo. (My University, 2014)
Abstract In recent years there has been a public uproar in Zimbabwe about the trafficking of children and resignation that not enough is being done to address the problem. External assessments also claim that there is little action on the prevention of trafficking, protection of victims and prosecution of offenders. The purpose of this study was to examine the severity of the problem and to assess the actions being taken currently by the key stakeholders. The study focused on trafficking for child prostitution in Harare province. The study found that child trafficking for prostitution is indeed taking place but that the response is weak, largely due to the fact that there is no legal framework on which to base such a response. Further the absence of a legal framework limits the ability of government to collaborate with and coordinate all the key stakeholders involved in the area of trafficking.
MM 2013
Keywords: Child trafficking,Child abuse,Children's rights.